Hypolipidemic and hypoglycemic nature of lactobacillus strains in fermented vegetable and dairy products - Ghatani, Kriti; Thapa, Subarna; Chakraborty, Priya (Frontiers in Food Science and Technology, 2022)
Fermented foods are functional foods with better nutritional and technological characteristics that prove numerous health benefits to the host as they harbor diverse group of microorganisms in them. There has been increased consumption of fermented vegetables, cereal based foods, dairy products, meat and fish products and rice based foods and beverages throughout the globe. Diseases like obesity, cardiovascular diseases and diabetes are the chief metabolic disorders that have become a leading concern of public health in the world. According to the World Health Organization statistics, approximately 422 million people, around the globe, suffer from diabetes, and about 2.6 million deaths, worldwide, have been caused due to raised cholesterol levels in humans. Although there is no doubt that low-fat and low-carbohydrate diets are an effective means of lowering blood cholesterol and managing blood sugar levels under experimental conditions, however, they appear to be less effective, owing to poor compliance, which can be linked to the diets’ low palatability and acceptability by consumers. Therefore, there is a need for novel strategies to mitigate the effects of raised blood glucose and blood cholesterol levels, also keeping in mind the consumer acceptability. Probiotic lactic acid bacterial supplements have gathered much attention in the prevention of diet induced metabolic diseases. Lactobacillus is the largest genus falling under the group of Lactic acid bacteria which includes approximately 300 species of bacteria and innumerable strains. Further, they have a long history of use in food fermentation and has also procured the “generally recognized as safe” status. This genus is accredited as probiotics due to their countless health-promoting effects on the host. They have been suggested to facilitate positive contribution to the nutritional, physiological, microbiological and immunological effect on the host. This paper focuses on the in vitro and in vivo studies of Lactobacillus probiotics reported from fermented vegetable and milk products in the treatment of obesity, diabetes and cardiovascular diseases.